Implications of avian flu for economic development in Kenya - Thurlow, James (International Food Policy Research Institute, 2010)
Kenya is vulnerable to avian flu given its position along migratory bird routes and proximity to other high-risk countries. This raises concerns about the effect an outbreak could have on economic development. We use a dynamic computable general equilibrium model of Kenya to simulate potential outbreaks of different severities, durations, and geographic spreads. Results indicate that even a severe outbreak does not greatly reduce economic growth. It does, however, significantly worsen poverty, because poultry is an important income source for poor farmers and a major food item in consumers' baskets. Avian flu therefore does pose a threat to future development in Kenya. Reducing the duration and geographic spread of an outbreak is found to substantially lower economic losses. However, losses are still incurred when poultry demand falls, even without a confirmed outbreak but only the threat of an outbreak. Our findings support monitoring poultry production and trade, responding rapidly to possible infections, and improving both farmers' and consumers' awareness of avian flu.